2021
DOI: 10.1108/lthe-09-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Improving Emirati students’ social responsibility competence through global citizenship education

Abstract: Purpose The purpose of this study is twofold: to determine if implementing a global citizenship education curriculum can aid the development of Emirati students’ social responsibility competence and to experiment with different instructional strategies that aim to yield improvement in the social responsibility of students. Design/methodology/approach The intervention research study used a mixed-methods quasi-experimental approach to examine Emirati students’ social responsibility gains and overall perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…In contrast, the statement with the lowest mean score was implementing training courses for students with low achievement in the education process and implementing training courses for students with low achievement in the educational process. This is contrary to the results by Wren (2021), who found that a "global citizenship education curriculum" helped the Emirati students to become more responsible for their communities. The study shows that a citizenship curriculum should be a part of community service courses for undergraduates by clearly linking classroom projects to current social challenges and fostering student conversation and reflection.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast, the statement with the lowest mean score was implementing training courses for students with low achievement in the education process and implementing training courses for students with low achievement in the educational process. This is contrary to the results by Wren (2021), who found that a "global citizenship education curriculum" helped the Emirati students to become more responsible for their communities. The study shows that a citizenship curriculum should be a part of community service courses for undergraduates by clearly linking classroom projects to current social challenges and fostering student conversation and reflection.…”
Section: Discussioncontrasting
confidence: 98%
“…It also says that other groups, such as parents, should be included. Wren (2021) found that the intervention study used a "global citizenship education curriculum" to help Emirati students become more responsible for their communities. There are strong indications that the civic attitudes and skills questionnaire (CASQ) can be used in the United Arab Emirates.…”
Section: Review Literaturementioning
confidence: 99%
“…Kramsch (2011) believes that along with the information, attitudes, and skills listed above, intercultural speakers should also possess linguistic and pragmatic competence, meaning they should be able to use language forms correctly and effectively. In addition, Byram and Fleming (1998;2021) suggested an intercultural speaker as "someone who knows of one or, preferably, more cultures and social identities and can discover and relate to new people from other contexts for which they have not been indirectly prepared." In actuality, the intercultural speaker can employ interpretation and relational abilities by using their cultural knowledge to analyze and contextualize texts from the target culture.…”
Section: Conceptualizing Intercultural Speakersmentioning
confidence: 99%
“…surrounding the language they speak are known as intercultural speakers.Byram and Fleming (1998;2021) defined intercultural speakers refers to the practice of facilitating understanding and engagement between individuals from different national and cultural origins through language use. Understand the nuances of cultural communication styles, customs, values, and norms.…”
mentioning
confidence: 99%
See 1 more Smart Citation